2019
DOI: 10.5513/jcea01/20.1.2215
|View full text |Cite
|
Sign up to set email alerts
|

Forage grass productivity and quality in south-western part of Pannonian basin

Abstract: The aim of the research was to compare the productivity and quality of several forage grasses in the climate conditions of southeastern Europe. The research was conducted during 2012 and 2013, in the southwestern part of the Pannonian basin (vicinity of Osijek, Croatia). The experiment included 5 grass species: Italian ryegrass (Lolium multiflorum), cocksfoot (Dactylis glomerata), hybrid ryegrass (Lolium x boucheanum), perennial ryegrass (Lolium perenne) and timothy (Phleum pratense) cut three times per year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In one of the most important forage legume -alfalfa the share of hard seeds after harvest is 23.3% [56]. After two years of storage, part of hard seeds decreased to 2.9%, and after 4 and 8 years of storage, hard seed is not registered.…”
Section: Changes In Seed Quality Of Perennial Forage Species As a Res...mentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the most important forage legume -alfalfa the share of hard seeds after harvest is 23.3% [56]. After two years of storage, part of hard seeds decreased to 2.9%, and after 4 and 8 years of storage, hard seed is not registered.…”
Section: Changes In Seed Quality Of Perennial Forage Species As a Res...mentioning
confidence: 99%
“…Total seed germination after two years of storage was 85.8%, after four year was 73.7%, and after the eighth year germination was 42.8%. Cultivars have behaved variably according to the contents of the hard and germinated seed in relation to the length of storage [56]. Effect of long-term natural aging on germinability and biochemical characteristics in two different clover (Trifolium repens and Trifolium pratense) showed that only two types of the old seeds showed a discernible increase in peroxidase activity during the germination of the legume seeds, but catalase activity dropped [57].…”
Section: Changes In Seed Quality Of Perennial Forage Species As a Res...mentioning
confidence: 99%
“…In alfalfa seeds, physical dormancy is present and still expressed in different climatic zones (Čupić et al, 2005;Zimmermann et al, 1998;Fairey and Lefkovitch 1991). According to Harrison et al, (2021), Xie et al, (2023), alfalfa seeds are characterized by a strong seed coat that does not allow the absorption of water and gases.…”
Section: Introductionmentioning
confidence: 99%